Comprehensive analysis of PIK3CA mutations in advanced colorectal cancer using circulating tumor DNA profiling - Allante Milsap; Jill Tsai; Baqir Jafry; Alex Kim; Syed Mohammad Ali Kazmi; Nilesh Verma (npj Precision Oncology)
Abstract Mutations in PIK3CA are prevalent in advanced colorectal cancer (CRC) and are associated with advanced-stage disease and poor prognosis. However, the prognostic value of these mutations remains unclear. To better understand their role in CRC progression, we evaluated the genomic landscape of PIK3CA mutations (PIK3CAm) in advanced CRC using plasma-based ctDNA from ~17,000 samples (Guardant360 database). Mutation co-occurrence, MSI-H status, TMB scores, and exon-specific mutation frequencies were analyzed. Our study shows that the frequency of PIK3CAm (19.2%) and distribution of exons 9 and 20 are similar to those found previously in the literature. Our results demonstrate PIK3CAm having a low frequency of MSI-H co-occurrence, higher TMB scores, and increased co-occurring alterations in APC, BRAF, EGFR, ERBB2 and KRAS, which may suggest higher genomic instability. Our findings underscore the clinical significance of PIK3CAm in CRC and supports the development of tailored therapeutic strategies targeting this mutation.